Nanostructured of Vanadium Phosphorus Oxide (VPO) Catalyst Prepared by Sonochemical Treatment - Yee Ching Wong (2011)
A series of six nanostructured vanadium phosphorus oxide catalysts were synthesized through the starting material vanadium pentoxide which subjected to high intensity ultrasound irradiation with different duration of time. XRD patterns of all nanostructed vanadium phosphorus oxide catalyst were perfectly indexed to (VO)2P2O7 with one additional small peak which corresponds to the present of small amount of V5+ phase except for the catalyst that undergo 120 min of ultrasound irradiation time. The surface morphologies shown in TEM of the catalysts synthesized were all in uniform, well defined shapes and surface structures in nano-scale range but tend to agglomerate with each other to form larger particles. Futhermore, high amount of active oxygen species were released from V4+ phase (O-V4+ pair) for the nanostructured VPO catalyst which were synthesized with 30 min of ultrasound irradiation time (SRVPO30) anddrastic increment in n-butane conversion (9%) in catalytic evaluation test, suggested that these nanostructured VPO is an active catalyst for partial oxidation of n-butane towards maleic anhydride.